Dental Tourism in India: A Twist in Modern Dentistry: Tourism, India, Dentistry - Khare, Anshika; Kushwah, Priyanka Singh (Journal of Orofacial Research, 2019)
The modern world is a witness in which oral diseases at their boom due to changes in lifestyle and food habits. Although awareness regarding dental problems increasing but it is very difficult to find a suitable way out to resolve them. As we know that the treatment of oral diseases are challenging due to its high financial outlook. Thus people wants to acquire a sound system to solve their oral problems with least expenditures and dental tourism might create the best opportunities to resolve all dental problems throughout the world. Here we review this article to enlighten the facts gazing on dental tourism that gives a twist in conventional dentistry.